2013
DOI: 10.1016/j.ajpath.2013.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Milky Spots Promote Ovarian Cancer Metastatic Colonization of Peritoneal Adipose in Experimental Models

Abstract: The goal of controlling ovarian cancer metastasis formation has elicited considerable interest in identifying the tissue microenvironments involved in cancer cell colonization of the omentum. Omental adipose is a site of prodigious metastasis in both ovarian cancer models and clinical disease. This tissue is unusual for its milky spots, comprised of immune cells, stromal cells, and structural elements surrounding glomerulus-like capillary beds. The present study shows the novel finding that milky spots and adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
132
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(145 citation statements)
references
References 53 publications
3
132
0
4
Order By: Relevance
“…Recently, we showed that O-ASCs promoted proliferation, migration, chemotherapy, and radiation response of ovarian cancer cells (8). Omentum has been shown to promote colonization of ovarian cancer cells (11). Mounting evidence suggests that bidirectional communication between ovarian cancer and its microenvironment is critical for tumor growth (12).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we showed that O-ASCs promoted proliferation, migration, chemotherapy, and radiation response of ovarian cancer cells (8). Omentum has been shown to promote colonization of ovarian cancer cells (11). Mounting evidence suggests that bidirectional communication between ovarian cancer and its microenvironment is critical for tumor growth (12).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other peritoneal adipose, omental adipose tissue contains unusual immune structures known as milky spots, which contain B, T, and NK cells and macrophages, which play key roles in peritoneal homeostasis 8,9 . In addition to their physiologic functions, we found that milky spots play an active role in ovarian cancer metastatic colonization 4 . In experimental metastasis assays, SKOV3ip.1, CaOV3, and HeyA8 (human) and ID8 (murine; C57BL/6) ovarian cancer cells rapidly home to milky spots, suggesting that the cells are moving toward a secreted chemotactic factor.…”
mentioning
confidence: 93%
“…The omentum is a preferred early site of HGSC metastasis [4][5][6][7] . Unlike other peritoneal adipose, omental adipose tissue contains unusual immune structures known as milky spots, which contain B, T, and NK cells and macrophages, which play key roles in peritoneal homeostasis 8,9 .…”
mentioning
confidence: 99%
See 2 more Smart Citations